Green Accounting, SDGs, and Profitability with Good Corporate Governance as a Moderating Variable - Adisty Inez Maheswary; Anita Wijayanti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The objective of this study is to investigate the influence of green accounting and Sustainable Development Goals on profitability in energy-sector companies with good corporate governance as a moderating variable. Using purposive sampling, 18 companies listed on the Indonesia Stock Exchange for the 2020-2024 period were selected, resulting in 90 data points. The Moderated Regression Analysis was applied using EViews 12. The results indicate that green accounting and Sustainable Development Goals do not affect profitability. Further, good corporate governance which is proxied by institutional ownership does not moderate the influence of green accounting on profitability but strengthens the effect of Sustainable Development Goals on profitability. These findings underscore that sustainability practices need to be integrated and supported by good corporate governance in order to enable it to contribute to profitability.